Aerodynamics of airfoil sections and their influence on wind turbine design and performance. (1st January 2012) - Abdelrahman, Mohammad; Hassanein, Atef
The primary goal of this work is to reflect the effectiveness of the aerodynamic characteristics of blade airfoil-sections on the design and overall performance predictions of the horizontal-axis wind turbines. A post-stall model has been introduced and used throughout the work to secure reliable data in a wide range of angles of attack. It has been found that the general performance requirement of such airfoils is to exhibit a maximum lift-coefficient which is relatively insensitive to roughness effects and to have a low minimum drag coefficient and/or a high lift/drag ratio. The contribution of these parameters at the blade-tip region is very high and almost equal to the contributions of the mid and root regions together. Consequently, the airfoil section should be designed/selected according to its location along the blade to ensure its highest contribution to the overall performance of the rotor.